Design and analysis of High-Speed Low-Power Vedic Multiplier with 3-1-1-2 compressor Using Reversible Logic gates. Issue 1 (February 2021) - Ms.Dharani, S; Satheesan, Mr.Abin; Asuvanti, M A; Kumar, Ranjith; Vidhya, S
Abstract: The FFT Function in digital signal processing is one of the most important function in several applications such as Image Processing, Wireless Communications and Multimedia. FFT Processors consisting of butterfly structure operations involving necessary operations such as Addition, Subtraction, and Multiplication of complex values. The FFT Butterfly Structure work is designed with a "Vedic Multipliers" for applications at high speed. In this Vedic Multiplier, an algorithm called "Urdhva Triyabhyam" was used to improve its efficiency by optimizing the number of logic gates, constant inputs and garbage outputs. The Data Computation time is reduced by an 3-1-1-2 compressor using reversible logic gates. Hence reducing the surplus power consumption of 11.24% and summation of the partial products is done with less delay factor of about 5.28%. The area, power, delay, area delay product and power delay product are calculated using cadence virtuoso and is implemented in Spartan-6 device family using Xilinx ISE.